'Alla Ricerca dei Plumcake Perduti': visual metaphors, satire, and intertextuality in ZeroCalcare's fumetti. Issue 2 (3rd March 2020) - Ursini, Francesco-Alessio
ABSTRACT: This paper presents an analysis of the works of fumetti ('comics') author ZeroCalcare and focuses on how these works blend different genres and themes, hence creating a complex conceptual network of intertextual relations. The paper addresses three research questions. The first question pertains to how these intertextual connections are created via the satirical use of characters and the complex visual metaphors they present. The second question pertains to how these connections situate ZeroCalcare's work within an Italian cultural and generational context. The third question pertains to how aspects of these connections can be defined as being formally specific to fumetti . The answers, based on a methodologically novel application of Metaphor Theory, suggest that the intertextual, metaphoric use of characters in ZeroCalcare's stories is possible due to the conceptual flexibility of fumetto as a medium, and to its connections to Italian culture.